Rhetoric beyond words : Delight and persuasion in the arts of the Middle Ages - Carruthers, Mary Jean, 1941- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"In the Middle Ages, liturgies, books, song, architecture and poetry were performed as collaborative activities in which performers and audience together realized their work anew. Essays by leading scholars analyse how the medieval arts invited and delighted in collaborative performances designed to persuade. The essays cast fresh light on subjects ranging from pilgrim processions within Chartres Cathedral, to polyphonic song, and the 'rhetoric of silence' perfected by the Cistercians. Rhetoric is defined broadly in this book to encompass its relationship to its sister arts of music, architecture, and painting, all of which use materials and media in addition to words, sometimes altogether without words. Contributors have concentrated on those aspects of formal rhetoric that are performative in nature, the sound, gesture, and facial expressions of persuasive speech in action. Delivery (performance) is shown to be at the heart of rhetoric, that aspect of it which is indeed beyond words" - Provided by publisher.
"Working by words alone" : the architect, scholasticism and rhetoric in thirteenth-century France / Paul Binski ; Grammar and rhetoric in late medieval polyphony : modern metaphor or old simile? / Margaret Bent ; Nature's forge and mechanical production : writing, reading and performing song / Elizabeth Eva Leach ; Rhetorical strategies in the pictural imagery of fourteenth-century manuscripts : the case of the Bohun psalters / Lucy Freeman Sandler ; Do actions speak louder than words? The scope and role of pronuntiatio in the Latin rhetorical tradition, with special reference to the Cistercians / Jan M. Ziolkowski ; Vultus adest (the face helps) : performance, expressivity and interiority / Monika Otter ; Special delivery : were medieval letter writers trained in performance? / Martin Camargo ; The concept of ductus, or journeying through a work of art / Mary Carruthers ; Ductus and memoria : Chartres cathedral and the workings of rhetoric / Paul Crossley ; Ductus figuratus et subtilis : rhetorical interventions for women in two twelfth-century liturgies / William T. Flynn ; Terribilis est locus iste : the Pantheon in 609 / Susan Rankin.
Includes bibliographical references and index.
Keywords: Rhetoric, Medieval; Geschichte 500-1500